"Falling in love with me means that she can never go back": a case study exploring the cumulative costs of multiple migrations. Issue 1 (2nd January 2023) - Kassan, Anusha; Nakamura, Nadine; Toews, Julia; Beks, Tiffany
Abstract: This case study centers on the narrative accounts of a lesbian couple in a binational relationship (i.e., two women from different countries) who left the United States (U.S.) at a time when immigration laws did not recognize their union. Given that they could not legally stay in the U.S. together, they immigrated to the Netherlands and subsequently to Canada. When DOMA was overturned and the couple was eligible to apply for immigration to the U.S., they opted to remain in Canada, in part due to the strain of multiple migrations . This concept has been described as the complex process that accompanies more than one immigration experience and the cumulative effect that this can have on couples and families over time, particularly when multiple resettlements have taken place. A descriptive case study methodology was employed to investigate the perceptions of multiple migrations of this lesbian binational couple, focusing mainly on their experiences in Canada. Specifically, individual interviews were conducted with each woman to explore their lived experiences of multiple migration and the impact this has had on various aspects of their lives, including those occurring at the intersection of privilege and oppression. A description of each woman is presented, followed by the significant themes that emerged from this study, including immigration difficulties and the centrality of relationship. Implications for psychological training, practice, research, policy were presented.